Basiscreme DAC: Characteristics and possibility of use for compounding drugs in pharmacy - Martinović Martina; Stanković Nina; Vuleta Gordana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2015)
Despite prescribing of industrially produced dermatological preparations, successful local treatment of certain diseases is still dependent on the knowledge and skills of pharmacists when compounding magistral and galenic drugs. Traditionally, dermatologists are those who prescribe these drugs most frequently, requiring from the pharmacist to compound a drug of a certain composition, by using appropriate excipients or a suitable base which are usually not prescribed by specialist. Basiscreme DAC which synonym is Amphiphilic cream, can be used as a base for compounding magistral drugs/preparations, and it is official by DAC/NRF 2013. Basiscreme DAC can be used for compounding of hydrophilic/lipophilic creams, topical emulsions and water-emulsifying ointments. Furthermore, it is suitable in compounding preparations used for subacute and chronic skin diseases and cosmetic products, as well. The aim of this work was to represent data from monograph in DAC/NRF, which are referring to composition, process of manufacture, characteristics, tests and usage of Basiscreme DAC for compounding of magistral drugs in pharmacies in Serbia, and also numerous pharmaceutical preparations of various drugs (dermatosteroids, dexpanthenol, isosorbide dinitrate etc.); relevant data can be found in DAC/NRF.